Cattaneo-Christov double diffusions theories with bio-convection in nanofluid flow to enhance the efficiency of nanoparticles diffusion. (August 2021) - Khan, Shan Ali; Waqas, Hassan; Naqvi, Syed Muhammad Raza Shah; Alghamdi, Metib; Al-Mdallal, Qasem
Abstract: Purpose: The current mathematical model is developed to scrutinize the consequence of bioconvective cross diffusion flow of magnetized viscous nanofluid past multiple geometries (cone, wedge and plate) with convective boundary conditions. Together the nanoparticles and motile microorganism are incorporated into the dimensionless nonlinear differential expressions. The behavior of Cattaneo-Christov heat and mass flux is accounted for energy and concentration expressions. The influence of activation energy and thermal radiation are considered. The mathematical model is reduced into an ordinary one by using adequate similarity transformation. Buongiorno model is utilized for nanofluid (nanoliquids) analysis. Methodology/approach: The renovated dimensionless self-similarity systems are then solved numerically by utilizing shooting technique built-in function bvp4c solver with the help of commercial software Matlab. The obtained results are verified and an outstanding agreement has been found. Engineering quantities of interest are observed physically. Findings: The features of various emerging parameters against velocity distribution, thermal distribution, and solutal field of species, microorganism concentration as well as skin friction coefficient, gradient of temperature, local Sherwood number and density number of motile microorganisms are interpreted and deliberated in tabulated and graphical form. Results: The results indicate that velocity field is raises via larger Grashof number. The resultant velocity is decline via larger magnetic parameter. Larger estimation of thermal Biot number increases the heat transfer. Larger thermal relaxation parameter reduces the temperature of fluid. The concentration of nanoparticles is declines via concentration relaxation parameter. The microorganism's field is declines by varying the variations of Peclet number.